Study of ALM-802 orto-alkoxi analogues cardiotropic activity - G. V. Mokrov; A. M. Likhosherstov; V. V. Barchukov; V. N. Stolyaruk; I. B. Tsorin; M. B. Vititnova; S. A. Kryzhanovskiy; T. A. Gudasheva (Фармакокинетика и Фармакодинамика, 2020)
New ortho-alkoxy analogs of the compound ALM-802 1a (N1-(2-methoxybenzyl)-N2-[2-((2-methoxybenzyl)amino)ethyl]ethane-1,2-diamine trihydrochloride) and 1b (N1-(2-ethoxybenzyl)-N2-[2-((2-ethoxybenzyl)amino)ethyl]ethane-1,2-diamine trihydrochloride), which differ from it by the presence of alkoxy groups in the phenyl rings only in the ortho positions. It was established that these structural changes lead to the disappearance of anti-ischemic activity. At the same time, antiarrhythmic activity was revealed in compound 1b on the models of aconitine and calcium chloride arrhythmias in rats (1 mg / kg, intravenously), which was absent in 1a.